Discrete multiporphyrin pseudorotaxane assemblies from di- and tetravalent porphyrin building blocks - Lohse, Mirko; von Krbek, Larissa K. S.; Radunz, Sebastian; Moorthy, Suresh; Schalley, Christoph A.; Hecht, Stefan (Beilstein Journal of Organic Chemistry, 2015)
Two pairs of divalent and tetravalent porphyrin building blocks carrying the complementary supramolecular crown ether/secondary ammonium ion binding motif have been synthesized and their derived pseudorotaxanes have been studied by a combination of NMR spectroscopy in solution and ESI mass spectrometry in the gas phase. By simple mixing of the components the formation of discrete dimeric and trimeric (metallo)porphyrin complexes predominates, in accordance to binding stoichiometry, while the amount of alternative structures can be neglected. Our results illustrate the power of multivalency to program the multicomponent self-assembly of specific entities into discrete functional nanostructures.
Keywords: crown ethers; multicomponent assembly; multivalency; porphyrins; pseudorotaxanes

Supramolecular Chemistry - Steed, J. W.; Atwood, J. L. (Wiley, 2007)

(untitled) - Lehn, J.-M. (Angew. Chem., Int. Ed., 1988)

(untitled) - Desiraju, G. R. (Angew. Chem., Int. Ed., 2007)

(untitled) - Hirst, A. R.; Escuder, B.; Miravet, J. F.; Smith, D. K. (Angew. Chem., Int. Ed., 2008)

(untitled) - Bhosale, R.; Mišek, J.; Sakai, N.; Matile, S. (Chem. Soc. Rev., 2010)

(untitled) - Zhao, Y.; Sakai, F.; Su, L.; Liu, Y.; Wei, K.; Chen, G.; Jiang, M. (Adv. Mater., 2013)

(untitled) - Cametti, M.; Crousse, B.; Metrangolo, P.; Milani, R.; Resnati, G. (Chem. Soc. Rev., 2012)

(untitled) - Valeur, B.; Leray, I. (Coord. Chem. Rev., 2000)

(untitled) - Flink, S.; van Veggel, F. C. J. M.; Reinhoudt, D. N. (J. Phys. Chem. B, 1999)

(untitled) - Beer, P. D.; Gale, P. A. (Angew. Chem., Int. Ed., 2001)

(untitled) - Martínez-Máñez, R.; Sancenón, F. (Chem. Rev., 2003)

(untitled) - Llinares, J. M.; Powell, D.; Bowman-James, K. (Coord. Chem. Rev., 2003)

(untitled) - Chen, Y.; Liu, Y. (Chem. Soc. Rev., 2010)

(untitled) - Feiters, M. C.; Rowan, A. E.; Nolte, R. J. M. (Chem. Soc. Rev., 2000)

(untitled) - Wang, L.; Li, L.-L.; Ma, H. L.; Wang, H. (Chin. Chem. Lett., 2013)

(untitled) - Huskens, J. (Curr. Opin. Chem. Biol., 2006)

(untitled) - Vigneron, J.-P. (Molecules, 1999)

Templated Organic Synthesis - Diederich, F.; Stang, P. J. (Wiley-VCH, 2000)

(untitled) - Whitesides, G. M.; Mathias, J. P.; Seto, C. T. (Science, 1991)

(untitled) - Safont-Sempere, M. M.; Fernández, G.; Würthner, F. (Chem. Rev., 2011)

(untitled) - He, Z.; Jiang, W.; Schalley, C. A. (Chem. Soc. Rev., 2015)

(untitled) - Mammen, M.; Choi, S.-K.; Whitesides, G. M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Mulder, A.; Huskens, J.; Reinhoudt, D. N. (Org. Biomol. Chem., 2004)

(untitled) - Fasting, C.; Schalley, C. A.; Weber, M.; Seitz, O.; Hecht, S.; Koksch, B.; Dernedde, J.; Graf, C.; Knapp, E.-W.; Haag, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Hunter, C. A.; Anderson, H. L. (Angew. Chem., Int. Ed., 2009)

(untitled) - Ercolani, G.; Schiaffino, L. (Angew. Chem., Int. Ed., 2011)

(untitled) - Papp, I.; Sieben, C.; Sisson, A. L.; Kostka, J.; Böttcher, C.; Ludwig, K.; Herrmann, A.; Haag, R. (ChemBioChem, 2011)

(untitled) - Kitov, P. I.; Sadowska, J. M.; Mulvey, G.; Armstrong, G. D.; Ling, H.; Pannu, N. S.; Read, R. J.; Bundle, D. R. (Nature, 2000)

(untitled) - Simanek, E. E.; McGarvey, G. J.; Jablonowski, J. A.; Wong, C.-H. (Chem. Rev., 1998)

(untitled) - Badjić, J. D.; Balzani, V.; Credi, A.; Lowe, J. N.; Silvi, S.; Stoddart, J. F. (Chem. – Eur. J., 2004)

(untitled) - Balzani, V.; Clemente-León, M.; Credi, A.; Lowe, J. N.; Badjić, J. D.; Stoddart, J. F.; Williams, D. J. (Chem. – Eur. J., 2003)

(untitled) - O’Sullivan, M. C.; Sprafke, J. K.; Kondratuk, D. V.; Rinfray, C.; Claridge, T. D. W.; Saywell, A.; Blunt, M. O.; O’Shea, J. N.; Beton, P. H.; Malfois, M.; Anderson, H. L. (Nature, 2011)

(untitled) - Kondratuk, D. V.; Perdigao, L. M. A.; O'Sullivan, M. C.; Svatek, S.; Smith, G.; O'Shea, J. N.; Beton, P. H.; Anderson, H. L. (Angew. Chem., Int. Ed., 2012)

(untitled) - Timko, J. M.; Moore, S. S.; Walba, D. M.; Hiberty, P. C.; Cram, D. J. (J. Am. Chem. Soc., 1977)

(untitled) - Ashton, P. R.; Campbell, P. J.; Glink, P. T.; Philp, D.; Spencer, N.; Stoddart, J. F.; Chrystal, E. J. T.; Menzer, S.; Williams, D. J.; Tasker, P. A. (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Ashton, P. R.; Chrystal, E. J. T.; Glink, P. T.; Menzer, S.; Schiavo, C.; Spencer, N.; Stoddart, J. F.; Tasker, P. A.; White, A. J. P.; Williams, D. J. (Chem. – Eur. J., 1996)

(untitled) - Jiang, W.; Schalley, C. A. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Clifford, T.; Abushamleh, A.; Busch, D. H. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Dong, S.; Zheng, B.; Wang, F.; Huang, F. (Acc. Chem. Res., 2014)

(untitled) - Amabilino, D. B.; Stoddart, J. F. (Chem. Rev., 1995)

(untitled) - Yamaguchi, N.; Gibson, W. H. (Chem. Commun., 1999)

(untitled) - Jiang, W.; Sattler, D.; Rissanen, K.; Schalley, C. A. (Org. Lett., 2011)

(untitled) - Balzani, V.; Credi, A.; Raymo, F. M.; Stoddart, J. F. (Angew. Chem., Int. Ed., 2000)

(untitled) - Kay, E. R.; Leigh, D. A.; Zerbetto, F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Vukotic, V. N.; Loeb, S. J. (Chem. Soc. Rev., 2012)

(untitled) - Liu, Y.; Flood, A. H.; Bonvallet, P. A.; Vignon, S. A.; Northrop, B. H.; Tseng, H.-R.; Jeppesen, J. O.; Huang, T. J.; Brough, B.; Baller, M.; Magonov, S.; Solares, S. D.; et al. (J. Am. Chem. Soc., 2005)

(untitled) - Coskun, A.; Banaszak, M.; Astumian, R. D.; Stoddart, J. F.; Grzybowski, B. A. (Chem. Soc. Rev., 2012)

(untitled) - Bruns, C. J.; Stoddart, J. F. (Acc. Chem. Res., 2014)

(untitled) - Romuald, C.; Busseron, E.; Coutrot, F. (J. Org. Chem., 2010)

(untitled) - Clark, P. G.; Day, M. W.; Grubbs, R. H. (J. Am. Chem. Soc., 2009)

The Colours of Life: An Introduction to the Chemistry of Porphyrins and Related Compounds - Milgrom, L. R. (Oxford University Press, 2001)

The Porphyrin Handbook - Ishii, K.; Kobayashi, N. (Academic Press, 2003)

(untitled) - Durot, S.; Taesch, J.; Heitz, V. (Chem. Rev., 2014)

(untitled) - Mandal, S.; Rahaman, M.; Sadhu, S.; Nayak, S. K.; Patra, A. (J. Phys. Chem. C, 2013)

(untitled) - Liu, Y.; Huang, Z.; Liu, K.; Kelgtermans, H.; Dehaen, W.; Wang, Z.; Zhang, X. (Polym. Chem., 2014)

(untitled) - Fathalla, M.; Strutt, N. L.; Barnes, J. C.; Stern, C. L.; Ke, C.; Stoddart, J. F. (Eur. J. Org. Chem., 2014)

(untitled) - Watanabe, K.; Kitagishi, H.; Kano, K. (Angew. Chem., Int. Ed., 2013)

(untitled) - Puglisi, A.; Purrello, R.; Rizzarelli, E.; Sortino, S.; Vecchio, G. (New J. Chem., 2007)

(untitled) - Králová, J.; Kejik, Z.; Břiza, T.; Poučková, P.; Král, A.; Martásek, P.; Král, V. (J. Med. Chem., 2010)

(untitled) - Kiba, T.; Suzuki, H.; Hosokawa, K.; Kobayashi, H.; Baba, S.; Kakuchi, T.; Sato, S.-I. (J. Phys. Chem. B, 2009)

(untitled) - Kano, K.; Kitagishi, H.; Dagallier, C.; Kodera, M.; Matsuo, T.; Hayashi, T.; Hisaeda, Y.; Hirota, S. (Inorg. Chem., 2006)

(untitled) - Kim, Y.-H.; Hong, J.-I. (Chem. Commun., 2002)

(untitled) - D'Souza, F.; Chitta, R.; Gadde, S.; Zandler, M. E.; Sandanayaka, A. S. D.; Araki, Y.; Ito, O. (Chem. Commun., 2005)

(untitled) - Even, P.; Boitrel, B. (Coord. Chem. Rev., 2006)

(untitled) - Zhang, H.; Liu, Q.; Li, J.; Qu, D.-H. (Org. Lett., 2013)

(untitled) - Jahan, M.; Safari, N.; Khosravi, H.; Moghimi, A.; Notash, B. (Polyhedron, 2005)

(untitled) - Imahori, H.; Fukuzumi, S. (Adv. Funct. Mater., 2004)

(untitled) - Imahori, H.; Sakata, Y. (Eur. J. Org. Chem., 1999)

(untitled) - Yong, C.-K.; Parkinson, P.; Kondratuk, D. V.; Chen, W.-H.; Stannard, A.; Summerfield, A.; Sprafke, J. K.; O'Sullivan, M. C.; Beton, P. H.; Anderson, H. L.; Herz, L. M. (Chem. Sci., 2015)

(untitled) - Parkinson, P.; Knappke, C. E. I.; Kamonsutthipaijit, N.; Sirithip, K.; Matichak, J. D.; Anderson, H. L.; Herz, L. M. (J. Am. Chem. Soc., 2014)

(untitled) - Liu, J.-Y.; Huang, Y.; Menting, R.; Röder, B.; Ermilov, E. A.; Ng, D. K. P. (Chem. Commun., 2013)

(untitled) - Menting, R.; Lau, J. T. F.; Xu, H.; Ng, D. K. P.; Röder, B.; Ermilov, E. A. (Chem. Commun., 2012)

(untitled) - Burrell, A. K.; Officer, D. L.; Plieger, P. G.; Reid, D. C. W. (Chem. Rev., 2001)

(untitled) - Yamada, Y.; Okamoto, M.; Furukawa, K.; Kato, T.; Tanaka, K. (Angew. Chem., Int. Ed., 2012)

(untitled) - van Nostrum, C. F.; Picken, S. J.; Schouten, A.-J.; Nolte, R. J. M. (J. Am. Chem. Soc., 1995)

(untitled) - Lindsey, J. S.; Schreiman, I. C.; Hsu, H. C.; Kearney, P. C.; Marguerettaz, A. M. (J. Org. Chem., 1987)

(untitled) - Geier, G. R., III; Lindsey, J. S. (Tetrahedron, 2004)

(untitled) - Jiang, W.; Schäfer, A.; Mohr, P. C.; Schalley, C. A. (J. Am. Chem. Soc., 2010)

(untitled) - Jiang, W.; Schalley, C. A. (J. Mass Spectrom., 2010)